Longevity Risk and Taxation of Public Pensions - Jukka Lassila; Tarmo Valkonen (Center for Economic Studies and ifo Institute (CESifo), 2015)
We study transitions from EET tax regime to TEE regime in a defined-benefit pension scheme with a numerical overlapping generations model, using stochastic mortality projections as inputs. In a traditional pension scheme with no automatic longevity rules, such as a link between life expectancy and pensions or retirement age, the tax regime shift can be used to improve public finances, when longevity increases. Diminished private saving and weaker labour supply incentives are among the downsides. Especially the latter makes the reform welfare-reducing, if the improvement in state finances is not used to relieve taxation of labour.
Keywords: H55; 330; taxation; pensions; longevity